Genetic analyses reveal independent domestication origins of the emerging oil crop Paeonia ostii, a tree peony with a long-term cultivation history - Li-Ping Peng (Nature Portfolio, 2017)
Abstract Paeonia ostii, a member of tree peony, is an emerging oil crop with important medical and oil uses and widely cultivated in China. Dissolving the genetic diversity and domestication history of this species is important for further genetic improvements and deployments. We firstly selected 29 simple sequence repeats (SSRs) via transcriptome mining, segregation analyses and polymorphism characterizations; then, 901 individuals from the range-wide samples were genotyped using well-characterized SSR markers. We observed moderate genetic diversity among individuals, and Shaanxi Province was identified as the center of genetic diversity for our cultivated plants. Five well-separated gene pools were detected by STRUCTURE analyses, and the results suggested that multiple independent domestication origins occurred in Shaanxi Province and Tongling City (Anhui Province). Taken together, the genetic evidence and the historical records suggest multiple long-distance introductions after the plant was domesticated in Shandong, Henan and Hunan provinces. The present study provides the first genetic evaluation of the domestication history of P. ostii, and our results provide an important reference for further genetic improvements and deployments of this important crop.